Dark nature : a natural history of evil - Watson, Lyall (New York : HarperCollinsPublishers, 1995)
A natural history of evil, looking at the origin and meaning of being wicked, and studying the dark side of nature from a biological standpoint, drawing on the author's own observations as a biologist and naturalist, and recent findings in evolutionary biology, anthropology, and psychology.
Includes bibliographical references (p. 293-308) and index.
Booklist.
Kirkus Starred.
Wilson's Public Library.
Adult
Keywords: Biology -- Philosophy; Evolution; Good and evil; Human beings; Philosophy of nature; Biology -- Philosophy; Evolution; Good and evil; Human beings; Natural theology